2020
DOI: 10.3390/e22111323
|View full text |Cite
|
Sign up to set email alerts
|

Optimization, Stability, and Entropy in Endoreversible Heat Engines

Abstract: The stability of endoreversible heat engines has been extensively studied in the literature. In this paper, an alternative dynamic equations system was obtained by using restitution forces that bring the system back to the stationary state. The departing point is the assumption that the system has a stationary fixed point, along with a Taylor expansion in the first order of the input/output heat fluxes, without further specifications regarding the properties of the working fluid or the heat device specificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
(51 reference statements)
0
11
0
Order By: Relevance
“…Therefore, the MOO solution set is not unique, and a series of feasible alternatives can be obtained, which are called Pareto frontiers. In this section, , , , and are used as objective functions; the compression ratio ( ) is used as an optimization variable; and NSGA-II [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] is used to perform bi-, tri-, and quadru-objective optimizations for an irreversible Diesel cycle. Through three different solutions, that is, LINMAP, TOPSIS, and Shannon entropy, the optimization results under different objective function combinations are obtained.…”
Section: Multi-objective Optimization With Power Output Thermal Efficiency Ecological Function and Power Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the MOO solution set is not unique, and a series of feasible alternatives can be obtained, which are called Pareto frontiers. In this section, , , , and are used as objective functions; the compression ratio ( ) is used as an optimization variable; and NSGA-II [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] is used to perform bi-, tri-, and quadru-objective optimizations for an irreversible Diesel cycle. Through three different solutions, that is, LINMAP, TOPSIS, and Shannon entropy, the optimization results under different objective function combinations are obtained.…”
Section: Multi-objective Optimization With Power Output Thermal Efficiency Ecological Function and Power Densitymentioning
confidence: 99%
“…Shi et al [ 44 ] and Ahmadi et al [ 45 ] performed MOO of the Atkinson cycle when the working fluid’s specific heats were constants [ 44 ] and varied with temperature non-linearly [ 45 ]. Gonzalez et al [ 46 ] performed MOO on , , and entropy generation of an endoreversible Carnot engine and analyzed the stability of the Pareto frontier. Ata et al [ 47 ] performed parameter optimization and sensitivity analysis for an organic Rankine cycle with a variable temperature heat source.…”
Section: Introductionmentioning
confidence: 99%
“…However, regarding the usefulness of the FTT, the endoreversible model has the merit of launching nowadays the competition of finding new upper bounds of thermal machines performance, closer to the real one. Thus, progress has been made in the modeling and optimization of thermodynamic processes and cycles [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], with special attention to the common ones in thermal machines: Otto cycle [ 27 ], Stirling engine [ 28 ], Kalina cycle [ 30 ], and Brayton cycle [ 31 , 32 ]. The results obtained [ 30 , 31 ] have shown that besides the gains of FTT optimization with three or four objectives, the original results reported in the initial work of the FTT theory [ 3 , 4 , 5 ] are also revealed.…”
Section: Introductionmentioning
confidence: 99%
“…After decades of development, a series of instructive and practical achievements have been obtained in finite time thermodynamics [1][2][3][4][5][6][7][8], the research objects of which include heat engines [9][10][11][12][13][14][15], refrigerators [16,17], heat pumps [18], chemical cycles [19], and quantum cycles [20,21]. The rectangular cycle (RC) is composed of four thermodynamic processes, its endothermic processes are closed to the endothermic processes of the dual cycle, and its exothermic processes are closed to the exothermic processes of the Miller cycle.…”
Section: Introductionmentioning
confidence: 99%